A Dual-Band Dual-Polarized Omnidirectional Antenna - Gu, Hui; Ge, Lei; Zhang, Jihong (Frontiers in Physics, 2020)
A dual-band dual-polarized omnidirectional antenna is investigated. The two bands are generated by a lower circular patch and an upper circular patch, respectively. A set of conductive vias and a coupled ring are utilized to widen the antenna bandwidth. Curved branches are introduced to contribute to circularly polarized radiation. A prototype was designed, fabricated and measured to demonstrate the performance of the antenna. Measured results show that an overlapped bandwidth of 15% from 2.22 to 2.58 GHz for both S11 ≤ -10 dB and axial ratio ≤ 3 dB is obtained in the low band, and an impedance bandwidth of 11.1% from 5.63 to 6.29 GHz is achieved in the high band. Measured peak gains are approximately 4.3 dBic and 5.4 dBi at two bands. Moreover, omnidirectional radiation patterns are also obtained within the operating band.